2018
DOI: 10.2147/imcrj.s177337
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Horner syndrome as a rare initial presentation of nasopharyngeal carcinoma: a case report

Abstract: BackgroundHorner syndrome refers to a set of clinical presentations resulting from disruption of sympathetic innervation to the eye and adnexa. Classically, the clinical triad consists of ipsilateral blepharoptosis, pupillary miosis, and facial anhidrosis. Ocular sympathetic denervation may signify life-threatening causes. Timely investigation and accurate diagnosis are essential in patients with oculosympathetic denervation.Case presentationA 33-year-old Asian man with a heavy smoking habit presented with a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…6 A case of 3 rd cranial nerve palsy as the presenting neurophthalmic feature of NPC has been reported by Beckmann et al 9 A study by Padungkiatsagul et al has reported isolated Horner's syndrome as the initial presentation of NPC. 12 But our patient did not have any miosis or anhidrosis. Studies by Agarwal et al Popovska et al have reported cranial nerve palsies due to cavernous sinus involvement in nasopharyngeal malignancies.…”
Section: Discussionmentioning
confidence: 50%
“…6 A case of 3 rd cranial nerve palsy as the presenting neurophthalmic feature of NPC has been reported by Beckmann et al 9 A study by Padungkiatsagul et al has reported isolated Horner's syndrome as the initial presentation of NPC. 12 But our patient did not have any miosis or anhidrosis. Studies by Agarwal et al Popovska et al have reported cranial nerve palsies due to cavernous sinus involvement in nasopharyngeal malignancies.…”
Section: Discussionmentioning
confidence: 50%
“…All papers that were gathered were either case series or case reports. A total of 20 articles were gathered, which included 57 patients (1,3,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) . These were analyzed in the first part of our study.…”
Section: Data Acquisitionmentioning
confidence: 99%